2017
DOI: 10.1088/1748-605x/aa6810
|View full text |Cite
|
Sign up to set email alerts
|

Performance of laser sintered Ti–6Al–4V implants with bone-inspired porosity and micro/nanoscale surface roughness in the rabbit femur

Abstract: Long term success of bone-interfacing implants remains a challenge in compromised patients and in areas of low bone quality. While surface roughness at the micro/nanoscale can promote osteogenesis, macro-scale porosity is important for promoting mechanical stability of the implant over time. Currently, machining techniques permit pores to be placed throughout the implant, but the pores are generally uniform in dimension. The advent of laser sintering provides a way to design and manufacture implants with speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 30 publications
0
41
0
1
Order By: Relevance
“…Recent studies comparing porous constructs and solid implants, both with clinically relevant surface treatments showed comparable mechanical force to failure even though porous implants had bone ingrowth whereas solid implants had bone on‐growth (Cheng, Humayun, Boyan, & Schwartz, ; Cheng, Humayun, & Cohen, ; Hyzy et al, ). These earlier studies did not examine the effects of differing porous architecture while maintaining pore size and porosity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies comparing porous constructs and solid implants, both with clinically relevant surface treatments showed comparable mechanical force to failure even though porous implants had bone ingrowth whereas solid implants had bone on‐growth (Cheng, Humayun, Boyan, & Schwartz, ; Cheng, Humayun, & Cohen, ; Hyzy et al, ). These earlier studies did not examine the effects of differing porous architecture while maintaining pore size and porosity.…”
Section: Discussionmentioning
confidence: 99%
“…In another interesting histomorphometric and microCT study, Cohen et al [ 26 ] compared the bone response to two different implants in the rabbit femur: laser sintered solid and porous implants. In this study, both microCT and histomorphometry showed significantly higher new bone volume for porous compared to solid implants, and bone growth was observed in porous implant pores, especially near apical portions of the implant [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another interesting histomorphometric and microCT study, Cohen et al [ 26 ] compared the bone response to two different implants in the rabbit femur: laser sintered solid and porous implants. In this study, both microCT and histomorphometry showed significantly higher new bone volume for porous compared to solid implants, and bone growth was observed in porous implant pores, especially near apical portions of the implant [ 26 ]. Accordingly, the authors concluded that laser sintered implants with micro/nanoscale surface roughness and trabecular porosity can stimulate new bone growth and may therefore be used as a superior alternative to solid implants for bone-interfacing implants [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…[53][54][55] AM technologies have been selected to manufacture Ti implants, customized subperiosteal Ti implants, [82][83][84][85][86] customized AM Ti meshes for bone grafting techniques, [87][88][89][90][91][92][93][94][95] Co-Co frameworks for implant impression procedures, 96,97 and Co-Cr and Ti implant frameworks for implant-supported prostheses. [98][99][100][101][102] With the introduction of AM technologies, different studies have analyzed the potential to manufacture Ti AM dental implants (Table 1), [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] customized designs that replicate the tooth's root shape (Table 2), [74][75]…”
Section: Application Of Am Technologies In Implant Dentistrymentioning
confidence: 99%
“…Furthermore, the mechanical properties, osteoconduction, and bone augmentation properties of titanium porous lattice structures have been evaluated. 102,103 Different in vitro and animal studies, 17,53,54,56,[60][61][62]64,72 as well as clinical studies 57,60,[65][66][67][68][69][70][71] have analyzed the utility of AM titanium implants. Authors concluded that AM technologies are an alternative for manufacturing custom implants, providing adequate and controlled porosity levels, superficial roughness that promotes new bone formation, and improves the osseointegration process.…”
Section: Application Of Am Technologies In Implant Dentistrymentioning
confidence: 99%